The Bobwhite Brigade: An Innovative Approach to Wildlife Extension Education - Dale Rollins (National Quail Symposium Proceedings, 2017)
A pilot program was initiated in 1993 to train high school youth in natural resource management and leadership skills with the goal of training them as "master volunteers." The "Bobwhite Brigade" was formed to educate youth about northern bobwhite (Colinus virginianus) biology and management needs. Cadets (high school sophomores and juniors) undergo an intensive curriculum in bobwhite biology, applied ecology, critical thinking skills and leadership development to equip them as spokespersons for wildlife management. Upon graduation from the Brigade, cadets are required to give > 3 educational programs to various audiences (youth and adult), and are provided incentives to give additional programs. Through 1996, 145 young people had graduated from the Brigade and presented approximately 1,200 educational programs. These programs have included newspaper and magazine articles, TV stories, public service announcements, and direct contacts through tours and field days. Quail Unlimited recognized the Bobwhite Brigade with its inaugural "Youth in Conservation Award" in 1994, and recognized the Brigade again in 1996 with another award. The Bobwhite Brigade model has served as a springboard for similar programs in > 6 other states. The underlying message reinforced throughout the Bobwhite Brigade is one of ecosystem management and how "the whole is greater than the sum of the parts." We have found that ecosystem management concepts can be delivered to high school youth in a very tangible manner with a very popular, non-controversial native wildlife species. This same model holds great potential for other youth camps where there is an emphasis on wildlife extension education.